2017
DOI: 10.1007/s10067-017-3589-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency as a risk factor for the development of autoantibodies in patients with ASIA and silicone breast implants: a cohort study and review of the literature

Abstract: The development of autoimmunity and/or autoimmune diseases is multifactorial. Vitamin D is one of the factors that might play a role. We postulated that both the presence of adjuvants and insufficient levels of vitamin D may result in the development of autoimmunity in patients with autoimmune/inflammatory syndrome induced by adjuvants (ASIA) in relation to silicone implant incompatibility. We measured vitamin D levels in 135 patients with ASIA in relation to silicone implant incompatibility and related findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 89 publications
(169 reference statements)
0
12
0
3
Order By: Relevance
“…In persons with a genetic predisposition, IL-6, TGF-β and Th-17 cells may convert an acute reaction into a chronic reaction, which may trigger systemic disease [ 7 ]. Some studies suggest that vitamin D deficiency [ 8 , 9 ] and pre-existing allergies [ 9 ] may be risk factors for the development of autoantibodies in patients with SBI. “Bleeding” of silicone outside the SBI capsule may further increase the risk of an autoimmunological reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In persons with a genetic predisposition, IL-6, TGF-β and Th-17 cells may convert an acute reaction into a chronic reaction, which may trigger systemic disease [ 7 ]. Some studies suggest that vitamin D deficiency [ 8 , 9 ] and pre-existing allergies [ 9 ] may be risk factors for the development of autoantibodies in patients with SBI. “Bleeding” of silicone outside the SBI capsule may further increase the risk of an autoimmunological reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study, vitamin D levels in silicone-implanted breast patients were shown to be inversely related to antibody levels (Relative risk 3.14, 95%CI: 1.24-7.59). 46 This result suggests the possible beneficial role of the immunomodulatory action of vitamin D in preventing the subsequent antibody formation in silicone-implanted patients.…”
Section: Silicone and Asia Syndromementioning
confidence: 91%
“…Stated more simply, the vast majority of silicone-induced ailments emanate from multiple and varied toxic disruptions of the body's biochemistry and have virtually nothing to do with autoimmunity (12,12,21) . Another recent publication by Tervaert and colleagues discusses factors that may contribute to the development of autoantibodies in implant recipients (27) . In actuality, the presence or absence of autoantibodies in patients with these devices has no relevance for diagnosing siliconeinduced disease (4,16,20,22) .…”
Section: Why Asia Is Fantasia (An Improvisation)mentioning
confidence: 99%